2020
DOI: 10.1002/cptc.202000089
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Singlet Fission Dynamics in Pentacene Ring‐Shaped Aggregate Models with Different Configurations

Abstract: Using the quantum master equation method, we investigate size and monomer configuration dependences of singlet fission (SF) in pentacene J-and H-type ring-shaped aggregate (N-mer) models. Interestingly, it is found that SF rates in the J-aggregate models monotonically decrease with increasing N, while those in the H-aggregate models show different variation behaviors depending on the parity of N, where the H-type pentamer model exhibits the maximum SF rate. It is also found that correlated triplet-pair yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…On the contrary, the TT′ states TT′(f)−TT′(j) correspond to the SA TT* basis in the order of increasing number of nodes, following the notation of our previous study on symmetric H-and J-aggregate models, 29,32 and TT′(f) and TT′(j) correspond to |TT N *⟩ and |TT N/2 * ⟩, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the contrary, the TT′ states TT′(f)−TT′(j) correspond to the SA TT* basis in the order of increasing number of nodes, following the notation of our previous study on symmetric H-and J-aggregate models, 29,32 and TT′(f) and TT′(j) correspond to |TT N *⟩ and |TT N/2 * ⟩, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…where H FE , H CT , H TT , and H int indicate the FE, CT, TT, and interaction Hamiltonians between different types of exciton states, respectively. 29,32 Here,…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study on pentacene J-type and H-type ring-shaped aggregates have concluded that the electronic coupling depends heavily on both the size and structure of the aggregate. 40 These findings show the importance of going beyond the dimer model. Furthermore, the influence of the environment has been studied previously in model crystals for tetracene and pentacene.…”
Section: Introductionmentioning
confidence: 94%